Improvement of the operations planning process using a hybridized fuzzy-multi-criteria decision-making approach - Petrović, Ivan; Milenković, Milan (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The possibility of optimizing decision making in the operations planning process in air defence units by applying a multi-criteria decision-making approach in a fuzzy environment is shown in the paper. By analyzing the content of the available literature, the selection criteria were determined based on which it is possible to evaluate and compare the courses of action of air defence units. The criteria are based on the evaluation parameters of the courses of action from the decision matrix in the phase of the operations planning process called the courses of action validation and comparison. Methods: The proposed approach combines the Laboratory for Testing and Evaluation of Decision Making (DEMATEL) and the Compressed Proportional Assessment (COPRAS) which have been successfully modified by fuzzy triangular sets. The fuzzy-DEMATEL method was applied to determine the criteria’s weights, and the fuzzy-COPRAS method was applied to evaluate the alternatives - courses of action. Results: Multiple fuzzy-multi-criteria decision-making methods were integrated into a unique model that can be applied in the operations planning process with the aim of optimizing the decision-making process. Conclusion: The paper contributes to military science in making decisions related to the operations planning process at the tactical level in air defence units.